High deuteron and neutron yields from the interaction of a petawatt laser with a cryogenic deuterium jet - Jiao, X.; Curry, C. B.; Gauthier, M.; Chou, H.-G. J.; Fiuza, F.; Kim, J. B.; Phan, D. D.; McCary, E.; Galtier, E. C.; Dyer, G. M.; Ofori-Okai, B. K.; Labun, L.; et al. (Frontiers in Physics, 2023)
A compact high-flux, short-pulse neutron source would have applications from nuclear astrophysics to cancer therapy. Laser-driven neutron sources can achieve fluxes much higher than spallation and reactor neutron sources by reducing the volume and time in which the neutron-producing reactions occur by orders of magnitude. We report progress towards an efficient laser-driven neutron source in experiments with a cryogenic deuterium jet on the Texas Petawatt laser. Neutrons were produced both by laser-accelerated multi-MeV deuterons colliding with Be and mixed metallic catchers and by d(d,n)^3He fusion reactions within the jet. We observed deuteron yields of 10^13/shot in quasi-Maxwellian distributions carrying 8-10% of the input laser energy. We obtained neutron yields greater than 10^10/shot and found indications of a deuteron-deuteron fusion neutron source with high peak flux (> 10^22 cm^-2 s^-1). The estimated fusion neutron yield in our experiment is one order of magnitude higher than any previous laser-induced dd fusion reaction. Though many technical challenges will have to be overcome to convert this proof-of-principle experiment into a consistent ultra-high flux neutron source, the neutron fluxes achieved here suggest laser-driven neutron sources can support laboratory study of the rapid neutron-capture process, which is otherwise thought to occur only in astrophysical sites such as core-collapse supernova, and binary neutron star mergers.